1995
DOI: 10.1165/ajrcmb.12.4.7695925
|View full text |Cite
|
Sign up to set email alerts
|

Induction of lipopolysaccharide-binding protein gene expression in cultured rat pulmonary artery smooth muscle cells by interleukin 1 beta.

Abstract: Lipopolysaccharide (LPS)-binding protein (LBP) binds with high affinity to LPS, and the LBP-LPS complex enhances cellular inflammatory responses to LPS. Although it is present in normal serum, LBP is also induced as part of the acute phase response. Synthesis of LBP is though to be limited to the liver, but we have recently reported significant extrahepatic (including pulmonary) LBP mRNA expression in in vivo rat models of sepsis and inflammation. In the present study, we tested the hypothesis that a cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…induce LBP expression by pulmonary vascular smooth muscle cells (27) and type II epithelial cells (28). In vivo, LBP levels were previously reported to be Ͼ100-fold higher in BALF obtained from asthmatic subjects following segmental allergen challenge compared with those in normal controls (12).…”
Section: Discussionmentioning
confidence: 97%
“…induce LBP expression by pulmonary vascular smooth muscle cells (27) and type II epithelial cells (28). In vivo, LBP levels were previously reported to be Ͼ100-fold higher in BALF obtained from asthmatic subjects following segmental allergen challenge compared with those in normal controls (12).…”
Section: Discussionmentioning
confidence: 97%
“…48 The inflammatory response induced by LPS is regulated by interleukins, such as IL-1 and IL-6 binding protein that were also up-regulated. 49 Acute toxicity by CT results in liver steatosis, centrilobular necrosis, and elevated serum enzymes released from damaged hepatocytes and chronic exposures cause cirrhosis and hepatocellular carcinoma. 50,51 CT is primarily metabolized to a peroxy radical by CYP2E1, resulting in an active metabolite responsible for increased lipid peroxidation.…”
Section: Compound Effects and Significant Genomic Changesmentioning
confidence: 99%
“…However, when the complementary DNA (cDNA) for rat LBP was cloned, Northern blot analysis of tissues from rats with acute phase reactions revealed an increased signal in the lung and kidney RNA, although the signal was much less intense than in liver RNA (39). Subsequently, Wong and coworkers showed that rat pulmonary artery smooth-muscle cells cultured in the presence of IL-1 ␤ produced an activity similar or identical to LBP (40). This established that LBP could be produced in the lungs, particularly in the setting of acute inflammation, but the biologic importance of LBP production by vascular smooth muscle cells required further study.…”
Section: Recognition Of Endotoxin In Normal and Inflamed Lungsmentioning
confidence: 99%